Study of the factors that promoted the implementation of Electronic Medical Record on iPads at Two Emergency Departments - Rao, Akhil Sanjay (American Medical Informatics Association, 2012)
The purpose of this study was to understand the factors which promoted the demand for iPads by physicians in two Emergency departments (ED) prior to a system wide implementation of an electronic medical record (EMR). A grounded theory design was employed and 14 semi-structured interviews conducted with ED physicians. Analysis of the interview transcripts was completed using Atlas.ti qualitative software, which revealed that physicians’ perceptions of iPad use in the ED stemmed from their personal use of iPads along with three perceived ease of use factors. Physicians perceived that improved patient physician interaction, improved workflow and structural iPad benefits promoted their demand. Physicians perceived the structural benefits of iPads would improve patient physician interaction and improve workflow in the ED. As interest in handheld devices such as iPads increases, these findings could direct and encourage other iPad implementations at other hospital EDs’.